Investigation of an Autofocusing Method for Visible Aerial Cameras Based on Image Processing Techniques - Zhichao Chen; Tao Zhang (International Journal of Aerospace Engineering)
In order to realize the autofocusing in aerial camera, an autofocusing system is established and its characteristics such as working principle and optical-mechanical structure and focus evaluation function are investigated. The reason for defocusing in aviation camera is analyzed and several autofocusing methods along with appropriate focus evaluation functions are introduced based on the image processing techniques. The proposed autofocusing system is designed and implemented using two CMOS detectors. The experiment results showed that the proposed method met the aviation camera focusing accuracy requirement, and a maximum focusing error of less than half of the focus depth is achieved. The system designed in this paper can find the optical imaging focal plane in real-time; as such, this novel design has great potential in practical engineering, especially aerospace applications.